EXPLORING THE RELATIONSHIP BETWEEN STUDENTS’ FRIENDS AND THE IMPACT ON DROP OUT RATES: A PSYCHOLOGICAL INVESTIGATION - Romanov, Elina (E-Journal VFU, 2025)
This study explores the intricate relationship between peer dynamics and student dropout rates in Israel. Results indicate notable differences between truant and non-truant students across various parameters related to peer relationships and academic performance. Non-truant students demonstrate higher connection levels, fewer attendance problems, and more shared activities, emphasizing the significance of maintaining connections within their peer group. Correlation analysis reveals positive relationships between interest similarity, connection with peers, and factors contributing to a supportive environment. Additionally, non-truant students exhibit a higher emphasis on the importance of friend support and tend to share more about school with their peers. Implications highlight the critical role of positive peer relationships in fostering academic and personal outcomes. Recommendations include strategies to promote positive connections, engage students in growth-oriented activities, and identify and support at-risk students. Acknowledging study limitations, this research provides actionable insights for educational stakeholders to address dropout causes and enhance positive outcomes for students.